18F-DCFPyL PET/CT in advanced high-grade epithelial ovarian cancer: A prospective pilot study - Metser, Ur; Kulanthaivelu, Roshini; Chawla, Tanya; Johnson, Sarah; Avery, Lisa; Hussey, Douglas; Veit-Haibach, Patrick; Bernardini, Marcus; Hogen, Liat (Frontiers in Oncology, 2022)
Objectives: Glutamate carboxypeptidase-II (GCP-II), a zinc metalloenzyme that resides in cell membrane, has been reported as overexpressed in the neovasculature of ovarian cancers. The study objective was to determine whether GCP-II targeted imaging with 18F-DCFPyL PET/CT can detect disease sites in women with advanced high-grade serous ovarian cancer (HGSOC). Materials and Methods: Twenty treatment-naïve women with advanced HGSOC were recruited (median age 60 years). Prior to commencing therapy (primary cytoreductive surgery [n=9] or neoadjuvant chemotherapy [n=11]), subjects underwent routine staging with contrast-enhanced abdominopelvic CT (=CT), followed by 18F-DCFPyL PET/CT (=PET). CT and PET were reported independently using a standardized reporting template assessing 25 sites. The performance of PET was compared to CT in all subjects and to surgery and surgical histopathology in 9 patients who underwent primary cytoreductive surgery. Results: Of the 25 sites assessed in 20 patients, CT detected disease in 292/500 (58.4%) locations and PET detected disease in 171/500 (34.2%). Compared to CT the sensitivity (95% CI) of PET to detect disease in the upper abdomen, the gastrointestinal tract or the peritoneum was 0.29 (0.20,0.40), 0.21 (0.11,0.33) and 0.74 (0.64,0.82), respectively. In the surgical cohort, 220 sites in 9 patients were evaluated. The sensitivity and specificity of CT and PET were 0.85 versus 0.54 (p<0.001) and 0.73 versus 0.93 (p<0.001), respectively. Conclusion: Although 18F-DCFPyL has higher specificity than CT in detecting advanced HGSOC tumor sites, it detects less disease sites than CT, especially in the upper abdomen and along the gastrointestinal tract, likely limiting its clinical utility.